Left cardiac sympathetic denervation in the management of long QT syndrome and catecholaminergic polymorphic ventricular tachycardia: A meta‐regression. (16th October 2019) - Sgrò, Alessandro; Drake, Thomas M.; Lopez‐Ayala, Pedro; Phan, Kevin
Abstract: Background: Left cardiac sympathetic denervation (LCSD) has been proposed as useful therapy for long QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia (CPVT), in addition to anti‐arrhythmic agents and implantable cardioverter defibrillators. This study aimed to assess the current evidence for LCSD and compare the open vs the video‐assisted thoracoscopic surgery (VATS) approaches. Methods: MEDLINE, Embase and Cochrane library databases were searched up to December 2018 for studies reporting the long‐term outcomes of LCSD in LQTS, CPVT patients. The incidence of cardiac events (CEs) before and after surgery, the change in QTc interval, and surgical complications were pooled to estimate the efficacy of LCSD. Meta‐regression was used to estimate the effects of surgical approach (open vs VATS) on outcomes following LCSD. Results: Twenty‐seven papers met our inclusion criteria (647 patients). VATS was used in 408 patients (63.1%), open surgery in 239 (36.9%). Mean follow‐up was 32.3 ± 32.5 months. Postsurgery, 398/585 patients (68.0%) were free of CEs and QTc decreased from 522 ± 61.6 ms to 494 ± 52.3 ms. Meta‐regression showed no differences between the two approaches in the incidence of CEs and surgical complications. VATS was associated with a smaller reduction in QTc ( β ‐coefficient −20.04, 95% CI −36.82 to −3.27, P  = .019). Conclusions: LCSD was associated with a reduction in the incidence of CEs in LQTS, CPVT patients and in the duration of QTc. Open surgery was associated with a greater reduction in QTc. Due to the limitations that hindered our study, a randomized trial is warranted to fully establish LCSD safety and efficacy.